AB0458 The Effect of Subcutaneously Administered Methotrexate on Mean Corpuscular Volume in the Treatment of Rheumatoid Arthritis. (10th June 2014) - Sames, E.; Li, C.; Roads, E.; Flanegan, K.; Zarkali, A.
Abstract : Background: Methotrexate (MTX) has been used for many years as treatment for Rheumatoid Arthritis (RA), and remains the first line disease modifying therapy with a well established efficacy and safety profile. Side effects include gastrointestinal (GI) symptoms, deranged liver function, pneumonitis and bone marrow suppression. Subcutaneous (SC) MTX offers improved tolerability and bioavailability when compared to oral MTX 1 . Patients with GI disturbances from oral MTX are often switched to the SC route. Other reasons for switching include mucositis, malaise and lack of efficacy on the maximum oral dose. Although few randomised controlled trials of parenteral versus oral MTX exist, the majority suggests a benefit to switching from oral to parenteral MTX 2 . MTX acts as a dihydrofloate reducatase inhibitor and therefore macrocytosis is a well recognised side effect. Although Azathioprine may also lead to macrocytosis 3 studies imply no link between this and overt bone marrow toxicity 4 and similar conclusion have not been reached with MTX either via the oral or SC route. Objectives: To determine whether MCV is affected by SC MTX in a cohort of RA patients in a district general hospital setting. Methods: Twenty nine patients with RA on SC MTX were analysed. Inclusion criteria were diagnosis of RA and treatment with SC MTX. All patients were treated with supplemental oral folic acid. Data was collected for the time period spanning September 2009 to December 2013. Macrocytosis is defined as an MCV of 100 or greater on five consecutive readings, or more than 105 on three readings. Results: The average duration of disease was 15.3 years. 9 of 29 (31%) patients on SC MTX demonstrated macrocytosis. Of these, 5 (17%) exhibited a higher than normal MCV on oral MTX before conversion to SC administration. Four (14%) became macrocytic on SC MTX, with a prior normal MCV on oral treatment. Of the 14% who showed macrocytosis on SC MTX the average Hb was 12.6g/dl. In the 20 patients who did not develop macrocytosis the average Hb was 12.4g/dl. Data were collected for potentially confounding factors such as vitamin B12 or folate deficiency, thyroid dysfunction and myeloma. Two of the fifteen patients who had raised MCV were found positive for one of these factors (low folate and high TSH). Conclusions: Only 14% of patients developed macrocytosis after conversion from oral to SC MTX. There was little difference in Hb between the patients who were macrocytic and those who were not. No overt case of anaemia was identified. None developed severe manifestations of bone marrow failure such as sustained pancytopenia. Our data suggest patients on SC MTX do not have a greater propensity to develop macrocytosis, and even in those who do there was no concurrent anaemia. More research on the implication of macrocytosis and SC MTX therapy is needed. References: Hoekstra et al. J Rheumatol. 2004 Apr;31(4):645-8. Moitra RK. Et al. 2005 Feb;44(2):256-7. Bernstein CNet al. DigDis Sci. 1994;39:1638–41 Thomas CW et al. Inflamm Bowel Dis. 2003;9:237–45 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2519